Gorge Motions of Acetylcholinesterase Revealed by Microsecond Molecular Dynamics Simulations - Cheng, Shanmei (Sci Rep, 2017)
Acetylcholinesterase, with a deep, narrow active-site gorge, attracts enormous interest due to its particularly high catalytic efficiency and its inhibitors used for treatment of Alzheimer’s disease. To facilitate the massive pass-through of the substrate and inhibitors, “breathing” motions to modulate the size of the gorge are an important prerequisite. However, the molecular mechanism that governs such motions is not well explored. Here, to systematically investigate intrinsic motions of the enzyme, we performed microsecond molecular dynamics simulations on the monomer and dimer of Torpedo californica acetylcholinesterase (TcAChE) as well as the complex of TcAChE bound with the drug E2020. It has been revealed that protein-ligand interactions and dimerization both keep the gorge in bulk, and opening events of the gorge increase dramatically compared to the monomer. Dynamics of three subdomains, S3, S4 and the Ω-loop, are tightly associated with variations of the gorge size while the dynamics can be changed by ligand binding or protein dimerization. Moreover, high correlations among these subdomains provide a basis for remote residues allosterically modulating the gorge motions. These observations are propitious to expand our understanding of protein structure and function as well as providing clues for performing structure-based drug design.